Bionic cardiovascular medicine. - Sugimachi, M. (IEEE Engineering in medicine and biology magazine)
A novel, bionic therapeutic strategy to treat various incurable cardiovascular diseases was developed. The bionic therapeutic strategy comprises a collection of methods to treat various diseases by replacing the native regulatory function or by correcting the abnormal native function with intelligent electronic devices. This paper presents the study on decoding the heart rate from the sympathetic nervous system, encoding pressor information and delivering it via nervous stimulation sequence, and improving the survival of animals with chronic heart failure by the correction of the abnormal cardiovascular regulatory function.